Bordetella bronchiseptica in Canine Respiratory Disease: A Review - Tridiganita Intan Solikhah; Ervina Astri Lestari; Andini Laila Ernadiani; Muhammad Akram (Journal of Advanced Veterinary Research, 2026)
Bordetella bronchiseptica is a major bacterial pathogen responsible for canine infectious respiratory disease complex (CIRDC), which affects the upper respiratory tract of dogs and contributes to significant morbidity in canine populations worldwide. The disease spreads primarily through aerosol and direct contact between infected and susceptible dogs, especially in environments with high animal density such as kennels, shelters, and dog daycare facilities. Puppies and immunocompromised dogs are particularly vulnerable due to their immature immune systems, while co-infections with respiratory viruses can exacerbate clinical signs and increase disease severity. Infected animals may shed the bacterium for extended periods, allowing continuous transmission even among clinically healthy carriers. Although human infection is rare, B. bronchiseptica poses a potential zoonotic risk, particularly for immunocompromised individuals, underscoring the importance of One Health approach that integrates animal, human, and environmental health. Preventive measures including intranasal vaccination, proper ventilation, strict hygiene, and public education are essential to reduce bacterial spread and disease incidence. Comprehensive control efforts combining vaccination programs, environmental management, and ongoing surveillance are critical to mitigate both animal health impacts and zoonotic transmission risks.